PENGARUH PENYULUHAN TERHADAP PENGETAHUAN SISTEM PENDIDIKAN TINGGI SISWA SMAN 8 KOTA TANGERANG, BANTEN - Herlin Tundjung Setijaningsih; Elda Selvira Dermawan; Richard Mikhael Ludony (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Students when choosing a school in high school need to continue their studies in college. Generally, they are still confused about choosing a study program and college. The purpose of this community service is to increase students' knowledge about the higher education system. Students' knowledge of the higher education system is very decisive in choosing study programs and universities, when high school students continue their studies. The method of implementing this activity is in the form of counselling. The activity partners were 95 11th grade students of SMAN 8 Tangerang City, Banten. Extension using zoom. Extension activities are carried out in the odd semester of 2021/2022. Data processing using SPSS software version 24. The results of community service activities show that there is a significant difference in students' knowledge about the higher education system before and after counselling. This proves that there is an effect of counselling on the knowledge of the higher education system of students.